2020
DOI: 10.1186/s13075-020-02233-9
|View full text |Cite
|
Sign up to set email alerts
|

Differential long-term retention of biological disease-modifying antirheumatic drugs in patients with rheumatoid arthritis by age group from the FIRST registry

Abstract: Background: The effectiveness and safety of biological disease-modifying antirheumatic drugs (bDMARDs) by age group (< 65, 65-74, and ≥ 75 years) are uncertain. We examined retention rates reflecting the effectiveness and safety of bDMARDs in actual clinical practice for clarifying optimal therapeutic strategies for rheumatoid arthritis (RA) by age groups. Methods: Data of patients who were treated with tumor necrosis factor inhibitors (TNFi), abatacept (ABA), and tocilizumab (TCZ) between February 2011 and Ap… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 57 publications
0
11
0
Order By: Relevance
“…A Belgian cohort study (sub-analysis of the ACTION study) also showed sustained long-term retention rates (up to 5-year retention) in RA patients treated with ABT [ 9 ]. ABT treatment has been reported to have relatively higher retention rates than other biologics [ 6 , 7 , 8 ]. A recent report has described that ABT treatment in elderly RA patients (≥75 years) had better 3-year retention rates than TNF inhibitors (FIRST registry) [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A Belgian cohort study (sub-analysis of the ACTION study) also showed sustained long-term retention rates (up to 5-year retention) in RA patients treated with ABT [ 9 ]. ABT treatment has been reported to have relatively higher retention rates than other biologics [ 6 , 7 , 8 ]. A recent report has described that ABT treatment in elderly RA patients (≥75 years) had better 3-year retention rates than TNF inhibitors (FIRST registry) [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…ABT treatment has been reported to have relatively higher retention rates than other biologics [ 6 , 7 , 8 ]. A recent report has described that ABT treatment in elderly RA patients (≥75 years) had better 3-year retention rates than TNF inhibitors (FIRST registry) [ 8 ]. However, several csDMARDs (not only MTX) are used in combination with ABT in daily clinical practice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerical studies employed "drug retention" for time-toevent analysis. [16][17][18] However, there are some issues regarding the definition of "event" and "censored for drug retention". Regarding the definition of drug retention, treatment discontinuation due to disease remission was also treated as an event.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, cohort-based observational studies may be more suitable to investigate the performance of bDMARDs among unique population such as EORA. There have been a few observational studies comparing the effectiveness of bDMARDs among elderly patients with RA [ 12 , 13 ]. These studies included not only EORA but young-onset RA who had relatively long disease duration.…”
Section: Introductionmentioning
confidence: 99%